2023
DOI: 10.3390/e25010134
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of Non-Linear Convection Diffusion Equations for a Rotating-Disc Electrode

Abstract: Rotating-disc electrodes (RDEs) are favored technologies for analyzing electrochemical processes in electrically charged cells and other revolving machines, such as engines, compressors, gearboxes, and generators. The model is based on the concept of the nonlinear entropy convection-diffusion equations, which are constructed using semi-boundaries as an infinite notion. In this model, the surrogate solutions with different parameter values for the mathematical characterization of non-dimensional OH− and H+ ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Alhakami et al [31] used hybrid artificial neural network approach and provided dynamical study of vector-borne viral plant diseases. Alarfaj et al [32] investigated computed stiff fractional modeling through a numerical technique for machine learning and a numerical quantitative study was carried out by Alshammari et al [33] in their paper having diffusion equations for nonlinear convection. Rahman and his coinvestigators [34] reported a nonlinear mass transfer in flow through a porous media-occupied channel with the aid of a numerical approach and hybrid heuristic paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Alhakami et al [31] used hybrid artificial neural network approach and provided dynamical study of vector-borne viral plant diseases. Alarfaj et al [32] investigated computed stiff fractional modeling through a numerical technique for machine learning and a numerical quantitative study was carried out by Alshammari et al [33] in their paper having diffusion equations for nonlinear convection. Rahman and his coinvestigators [34] reported a nonlinear mass transfer in flow through a porous media-occupied channel with the aid of a numerical approach and hybrid heuristic paradigm.…”
Section: Introductionmentioning
confidence: 99%